CONTENT OF PROTEIN AND GLUTEN FRACTIONS OF SOFT WINTER WHEAT VARIETIES OF INTENSIVE TYPE RECEIVED IN I.G. KALINENKO ARRIGC - N. S. Kravchenko; N. N. Vozhzhova; N. G. Ignatieva; E. V. Ionova; A. P. Samofalov (Зерновое хозяйство России, 2018)
The article gives the results of the study of protein and gluten fractions of soft winter wheat varieties of intensive type in their dynamics. We have considered varying of the traits ‘protein fraction’ and ‘gluten fraction’ during 10 years and a coefficient of their correlation. We have estimated content of protein and gluten fraction of 11 soft winter wheat cultivars on average for 10 years and in each year. The cultivars ‘Aksiniya’ and ‘Tanais’ showed high average content of protein fraction and a slight variability of the trait during the years with 15,2%; V – 4,6%  and 15,3%; V – 5,1% respectively. The cultivars ‘Aksiniya’ (29,4%; V – 7,5%), ‘Tanais’ (28,7%; V - 7,2%), ‘Marafon’ (28,0%; V - 7,6%) and ‘Rostovchanka 7’ (27,4%; V - 8,0%) showed average content of gluten fraction and a slight variability of the trait during the years. The cultivars ‘Rostovchanka 3’(15,6%), ‘Donskaya Yubileynaya’ (15,5%) and ‘Tanais’ (15,3%) showed the largest protein fraction on average during 10 years. The cultivars ‘Donskaya Yubileynaya’ (30,6%), ‘Aksiniya’ (29,4%), ‘Rostovchanka 3’ (28,7%) and ‘Tanais’ (28,7%) showed the largest gluten fraction on average during 10 years. We recommend using the cultivars ‘Aksiniya’, ‘Tanais’, ‘Rostovchanka 3’ and ‘Donskaya Yubileynaya’ to improve the grain quality of soft winter wheat. We have carried out the analysis of the content of protein and gluten fractions depending on the amount of precipitations and active temperatures during the period of earing and maturation in the years of study.